2016
DOI: 10.1111/all.12943
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome and its impact on gastrointestinal atopy

Abstract: The prevalence of allergic conditions has continuously increased in the last few decades in Westernized countries. A dysbiotic gut microbiome may play an important role in the development of allergic diseases. Genetic, environmental and dietary factors may alter the commensal microbiota leading to inflammatory dysregulation of homeostasis. Murine and human studies have begun to elucidate the role of the microbiota in the pathogenesis of atopic diseases including asthma, atopic dermatitis and food allergies. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 69 publications
0
43
0
15
Order By: Relevance
“…Immunomodulatory effects are known for certain fibers, fats, proteins, iron, zinc, copper, selenium, vitamins A, C, D, B6, and B12, omega 3 and 6 fatty acids and folate. [2][3][4][5] Thus, nutrition may have an allergy-protective or allergy-provoking effect.…”
Section: The Relationship Of Habitual Diet With Esophageal Inflammatimentioning
confidence: 99%
See 1 more Smart Citation
“…Immunomodulatory effects are known for certain fibers, fats, proteins, iron, zinc, copper, selenium, vitamins A, C, D, B6, and B12, omega 3 and 6 fatty acids and folate. [2][3][4][5] Thus, nutrition may have an allergy-protective or allergy-provoking effect.…”
Section: The Relationship Of Habitual Diet With Esophageal Inflammatimentioning
confidence: 99%
“…Allergies are on the rise in western countries and the prevalence of food allergy has reached approximately 7% in children in the United States, 1 makingimproved diagnostics an important goal. Not all known potential allergens of wheat have been characterized so far and the prevalence of true wheat allergy is difficult to determine due to IgE crossreactivity with grass pollen allergens 2.…”
mentioning
confidence: 99%
“…При физиологическом течении родов происходит инверсия иммунного ответа эффекторных клеток CD4+ с формированием баланса Th1/Th2 и развитием иммунологической толерантности [15]. В этом физиологическом процессе большое значение играет микробиота кишечника, состав которой зависит от типа родоразрешения (вагинальные роды или кесарево сечение) и вида вскармливания (естественное или искусственное) [15][16][17]. Для детей с наследственной предрасположенностью к аллергии при мультифакториальном воздействии существенных факторов риска, таких как Одним из важнейших факторов риска формирования ранней сенсибилизации является характер вскармливания новорожденного ребенка.…”
Section: интранатальный и неонатальный периодыunclassified
“…Microbiome content of stool samples has the potential to be a non-invasive biomarker for disease diagnosis and monitoring. Previous studies observed differences in the microbiome of patients with EoE, but it is unclear how this is associated with patientoutcomes [31]. …”
Section: Pilot/demonstration Clinical Research Programmentioning
confidence: 99%